Beyond adjuvants: Antagonizing inflammation to enhance vaccine immunity. (8th June 2015) - Alter, Galit; Sekaly, Rafick Pierre
Abstract: Since the development of the first vaccine over 200 years ago, vaccines have saved millions of lives and have become the most cost-effective modern medical intervention. However, over 70 years ago, Freund recognized that the effectiveness of the vaccine-induced immune responses could be vastly improved via the co-delivery of inflammation-induced agents, giving birth to the adjuvant field. Since the first description of adjuvants, revolutionary discoveries, including the discovery of dendritic cells and pattern recognition receptors, that drive remarkably different biological profiles, have opened the landscape of opportunities for the development of novel adjuvants able to trigger a remarkably diverse inflammatory profiles, thereby qualitatively and quantitatively skewing adaptive immunity in a tailored manner against target pathogens. However, mounting data point to a critical role for pre-existing inflammation as a predictor of vaccine responsiveness. Thus, in this review we will discuss novel opportunities by which pre-existing inflammation may be modulated, skewed, or tuned via next-generation vaccine approaches to enhanced vaccine-induced immunity in the elderly, immunocompromised, or subjects with chronic diseases.